2018
DOI: 10.3390/ijms19082424
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Gastric Cancer: A Summary of Analogous Contributing Factors for Its Molecular Pathogenicity

Abstract: Gastric cancer is the third leading cause of cancer-related deaths and ranks as the fifth most common cancer worldwide. Incidence and mortality differ depending on the geographical region and gastric cancer ranks first in East Asian countries. Although genetic factors, gastric environment, and Helicobacter pylori infection have been associated with the pathogenicity and development of intestinal-type gastric cancer that follows the Correa’s cascade, the pathogenicity of diffuse-type gastric cancer remains most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 157 publications
0
67
0
1
Order By: Relevance
“…In the present study, no difference in miRNA expression was found within intestinal and diffuse type tumors except for miR-26a. Although intestinal type and diffuse type are thought to be caused by distinct mechanisms 31,32 , H. pylori infection is related to gastric carcinogenesis in both Lauren types 33 , and H. pylori infection is known to be associated with miRNA expression patterns 3,20,21,34 . Given these observations, we hypothesize that H. www.nature.com/scientificreports www.nature.com/scientificreports/ pylori and miRNA expression may be associated with field cancerization regardless of Lauren's classification.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no difference in miRNA expression was found within intestinal and diffuse type tumors except for miR-26a. Although intestinal type and diffuse type are thought to be caused by distinct mechanisms 31,32 , H. pylori infection is related to gastric carcinogenesis in both Lauren types 33 , and H. pylori infection is known to be associated with miRNA expression patterns 3,20,21,34 . Given these observations, we hypothesize that H. www.nature.com/scientificreports www.nature.com/scientificreports/ pylori and miRNA expression may be associated with field cancerization regardless of Lauren's classification.…”
Section: Discussionmentioning
confidence: 99%
“…This disproportion may be primarily genetically determined, specifically alterations in the CDH1 gene, which predispose individuals to GC at a young age with a diffuse phenotype. Diffuse-type GC lacks intercellular adhesion, which is often observed with diffuse invasion growth patterns throughout the stroma, characterized by rapid disease progression, being highly metastatic [68].…”
Section: More Aggressive Tumormentioning
confidence: 99%
“…Furthermore, intestinal metaplasia and intestinal-type gastric cancer also showed a relatively high frequency of alteration of the CDH1 gene [42]. Accordingly, mutational alterations of p53 and other factors may be associated with diffuse-type gastric cancer, as well as dysregulation of E-cadherin [37]. strong tendency of a lower location in Barrett-type adenocarcinoma.…”
Section: Chronic Active Gastritis-atrophic Gastritis (Mucosal Remodelmentioning
confidence: 97%
“…E-cadherin is important in maintaining cell-cell adhesion, cell survival and cell migration for tissue morphogeneis and homeostasis. Non-phosphorylated CagA of H. pylori binds E-cadherin or causes mutational alterations in p53 and hyper-methylation of the E-cadherin (CDH1) gene, resulting in the dissociation of the E-cadherin-β-catenin complex or the impairment of E-cadherin synthesis [37]. In diffuse-type gastric cancers, mutations in or hyper-methylation of the CDH1 gene is frequently found, suggesting disruption of E-cadherin function [38][39][40].…”
Section: Chronic Active Gastritis-atrophic Gastritis (Mucosal Remodelmentioning
confidence: 99%